Association of Hepatitis-B virus infection status with survival and treatment response in non-small cell lung cancer patients on anti‐pd‐1/pd-l1 therapy - Eda Alp; Goncagul Akdag Topal; DENİZ IŞIK; Nedim Turan (Journal of Global Antimicrobial Resistance)
AIM: HBV reactivation is a significant risk for cancer patients undergoing immunosuppressive or chemotherapy. However, since these patients are often excluded from immunotherapy trials, the safety of anti-PD-1 and anti-PD-L1 therapies in this context remains unclear. Recent advances in cancer treatment include immune checkpoint inhibitors (ICIs) like nivolumab, which are used in various cancers. This study explores the impact of HBV on survival and treatment response in metastatic non-small cell lung cancer (NSCLC) patients receiving anti-PD-1/PD-L1 therapy. METHODS: We retrospectively analyzed metastatic NSCLC patients undergoing anti-PD-1/PD-L1 therapy, examining their characteristics, HBV serology, treatment response, and mortality.Patients were categorized into two groups based on HBV serology: Anti-HBc+ and Anti-HBc-.We compared their disease progression and mortality rates.Overall survival (OS) and progression-free survival (PFS) were assessed using Kaplan-Meier analysis, with p-values < 0.05 considered statistically significant. RESULTS: 241 patients were included in the study. All patients were diagnosed with metastatic NSCLC. 99 (41%) patients had disease progression and 107 (44%) patients had mortality (Table-1). When divided into two groups according to hepatitis B serology, 49 patients were Anti-HBc+ and 192 patients were AntiHbc-. When these two groups were compared according to their mortality, a statistically significant difference was found in the AntiHBc+ group (Table-2). When OS and PFS data were compared according to serology, the survival rate was statistically significantly higher in the AntiHbc+ group(Table-3). CONCLUSIONS: Our findings indicate that patients with Anti-HBc+ status may have higher PD-L1 expression compared to those without chronic HBV infection, potentially leading to better responses to anti-PD-1/PD-L1 therapy.